Process evaluation of enhancing primary health care for non-communicable disease management in Malaysia: Uncovering the fidelity & feasibility elements. - Lee Lan Low; Fathullah Iqbal A B Rahim; Nur Aqlili Riana Hamzah; Mohd Safiee Ismail (PLoS ONE)
Background In combating the increasing trend of non-communicable diseases (NCDs) over the last two decades in the country, the Ministry of Health Malaysia developed the Enhanced Primary Health Care (EnPHC) initiative to improve care management across different levels of the public service delivery network. An evaluation research component was embedded to explore the implementation issues in terms of fidelity, feasibility, adaptation and benefit of the initiative's components which were triage, care coordination, screening, risk management and referral system. Methods A mixed methods study was conducted at 20 participating EnPHC clinics in Johor and Selangor, two months after the intervention was initiated. Data collected from self-reported forms and a structured observation checklist were descriptively analysed. In-depth interviews were also conducted with 20 participants across the clinics selected to clarify any information gaps observed in each clinic, and data were thematically analysed. Results Evaluation showed that all components of EnPHC intervention had been successfully implemented except for the primary triage counter and visit checklist. The challenges were mainly discovered in terms of human resource and physical structure. Although human resource was a common implementation challenge across all interventions, clinic-specific issues could still be identified. Among the adaptive measures taken were task sharing among staff and workflow modification to match the clinic's capacity. Despite the challenges, early benefits of implementation were highlighted especially in terms of service outcomes. Conclusions The evaluation study disclosed issues of human resource and physical infrastructure when a supplementary intervention is implemented. To successfully achieve a scaled-up PHC service delivery model based on comprehensive management of NCDs patient-centred care, the adaptive measures in local clinic context highlight the importance of collaboration between good organisational process and good clinical practice and process.